Optimizing Hajj Fund Management through Strategic Asset Allocation in Islamic Finance Instrument - Masruroh, Aini; Rodoni, Ahmad; Pontjowinoto, Iwan P (Faculty of Economic and Business Syarif Hidayatullah State Islamic University of Jakarta, 2023)
The management of Hajj funds must be done effectively using a rigorous standardized risk management approach. This study aims to create a Hajj fund management model using Islamic financial instruments through the optimal portfolio method and strategic asset allocation. The model was built using historical data from 2010–2022, involving Islamic deposits, government sukuk (SBSN), corporate sukuk, and Islamic stocks, which were analyzed with the Markowitz portfolio equation in Excel Solver. The result showed that the optimal portfolio yields an 8.50% expected return with a 4.00% risk; strategic asset allocation produces an 8.25% return with a 2.99% risk. The policy implication of this research is the need to review the initial deposit of pilgrims and explore alternative investments to bridge the gap between the actual cost of Hajj and pilgrims' payments while improving returns.JEL Classification: M31, M37, L92 How to Cite:Masruroh, A., Rodoni, A., & Pontjowinoto, I. P. (2023). Optimizing Hajj Fund Management through Islamic Finance Instrument. Signifikan: Jurnal Ilmu Ekonomi, 12(2), 287-306. https://doi.org/10.15408/sjie.v12i2.34403.